Intra-Articular Slow-Release Triamcinolone Acetonide from Polyesteramide Microspheres as a Treatment for Osteoarthritis - Anna Tellegen; Martijn Beukers; Imke Rudnik-Jansen; Nicolien van Klaveren; Kan Loi How; Nina Woike; George Mihov; Jens Thies; Erik Teske; Laura Creemers; Marianna Tryfonidou; Björn Meij (MDPI AG, 2021)
Osteoarthritis (OA) is a common cause of pain and disability. Local corticosteroid injections are effective in treating OA pain and inflammation but are short-acting. Prolonged intra-articular (IA) corticosteroid exposure may even lead to cartilage deterioration. The aim of this prospective study was to assess safety and provide proof-of-concept of IA-applied biodegradable polyesteramide-based microspheres (PEAMs) gradually releasing triamcinolone acetonide (TA). Mimicking continuous exposure associated with local drug delivery in canine articular chondrocytes cultured in the continuous presence of TA tissue regeneration was not affected, whereas intermittent exposure reduced proteoglycan production. In this respect, TA-PEAMs administered IA in a proof-of-concept study in 12 client-owned dogs with established OA also showed safety by radiographic examination, without changes in OA severity and in glycosaminoglycan synovial fluid levels. Treatment also resulted in clinical improvement in 10 out of 11 dogs during the two-month follow-up period, which persisted in 6 out of 10 dogs after 6 months, based on objective gait analysis and owner questionnaires. Synovial prostaglandin E2, a pro-inflammatory marker, was decreased two months after treatment. This study showed safety and proof-of-concept of IA-administered TA-PEAMs in dogs with OA, as a first step towards translation into the veterinary and human clinic.